Citizen science and the public nature of climate action. (3rd July 2019) - Groulx, Mark; Fishback, LeeAnn; Winegardner, Amanda
ABSTRACT: International efforts to implement the Paris Agreement call for unprecedented levels of collaboration to address one of society's most pressing crises. In this study we take the position that climate action work is very public work, in that decarbonization requires significant effort to learn together in ways that change commitments to enact environmental stewardship. To better understand this challenge, we examined citizen science as a space where climate action work is also the work of knowledge co-creation. Pre–post experience surveys and interviews with citizen scientists illustrate the transformative potential of place-based climate learning. Findings suggest that the relationships individuals developed with specific scientists and their personalized approaches to conducting science impacted how individuals related to the responsibility of environmental stewardship. This study highlights how effective, impactful collaboration is enriched when professionals share who they are in the context of the climate action work they do.